DYNAMICS OF EROSION PROSION PROCESS AND ITS ECOLOGICAL AND ECONOMIC ASSESSMENT - Butenko, Y. V.; Kharitonenko, R. A. (Land Management, Cadastre and Land Monitoring, 2012)
Dynamics of development of erosive process on lands of agricultural purpose of local level caused by water erosion is investigated. Calculation of an ecological and economic assessment of the damage to agricultural production with development of erosive process are carried out.